Estrategias de revitalización urbana para el edificio antigua industria de Licores del Valle y su contexto inmediato. (2020)
Industrial buildings from the point of view of their use, with the transcendence of time have fallen into abandonment and physical space detriment, which is why the conservation and integration of cultural heritage to the urban activities of a place is vital. In this way, today, adopting intervention actions must be confronted with the safeguarding of cultural heritage and added to this, the participatory and collective combination of the population and its urban context. The research focuses on the study of urban revitalization strategies that manage to form an urban fabric for the building of the old Liquor Industry of the Valley and its immediate context in the city of Santiago de Cali. Therefore, to create urban revitalization strategies, they must provide the conservation of the cultural heritage and sociocultural development of their spaces and their urban content.